Pendidikan karakter kerja sama dalam pembelajaran siswa Sekolah Dasar pada kurikulum 2013 - Silvy Dwi Yulianti; Ery Tri Djatmika; Anang Santoso (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
This research aims to describe the character education cooperation that occurred in the learning curriculum of elementary school students in 2013. The study was conducted by literature studies and preliminary study in four schools in the city of Malang in order to adjust the results of the study of literature with the circumstances that happened at school. The review of the literature it is known that the character of cooperation can improve the ability to interact and confidence of students. However, in practice found any constraint from outside and within the educational environment. Constraints on the outside in the form of social changes that change the values, norms, culture becomes a free nation, while the constraints thatcome from within the education environment includes mind-set, education policy and curriculum. This is consistent with the results of a preliminary study in which the implementation of character education curriculum in 2013 is still oriented on the ability of students' knowledge, attitudes and skills while the ability is still not integrated in acomprehensive manner.Keywords: Character education, Collaboration, Curriculum 2013 http://dx.doi.org/10.17977/um022v1i12016p033